Perancangan Aplikasi Game 2D "Tapping Bird" Menggunakan Construct 3 Berbasis Android - Martsad Ayyash; Deanna Durbin Hutagalung (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Game development is currently very fast with various game genres including the arcade game Flappy Bird created by Nguyen Ha Dong in 2013 and is successfully enjoyed by all ages. However, this Flappy Bird Game still has problems, namely there are two first things, Flappy Bird does not provide instructions on how to play the Flappy Bird game which causes players to lose at the beginning. both Flappy Bird games only have obstacles through the pipe, therefore it is necessary to design a game that can improve the shortcomings of the Flappy Bird game. This study aims to design the Tapping Bird arcade game that can perfect the Flappy Bird game and create arcade game innovations that are enjoyed by all ages. The method used is the Multimedia Development Life Cycle (MDLC) method with six stages, namely: concept, design. design), material collecting, assembly, testing, and distribution, using the Construct 3 tool. The results of the research can be designed for the Tapping Bird arcade game using the Android operating system. The Tapping Bird Game succeeded in perfecting the Flappy Bird Game with a Help Menu on how to play the game and innovate the enemy to attack the player, the results of the satisfaction rating by 30 respondents were 1118 (74.5%), respondents were satisfied with the Tapping Bird game. Based on the results of the study, it can be concluded that the arcade game "Tapping Bird" has perfected the Flappy Bird game and provides satisfaction as a game that entertains all ages.